2021
DOI: 10.3390/nu13072156
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Mellitus and Associated Factors in Slovakia: Results from the European Health Interview Survey 2009, 2014, and 2019

Abstract: Diabetes mellitus (DM) is a high-risk non-communicable disease with an emerging burden for the European Union (EU) member states in the past decades. The unfavorable trend of the burden is striking compared to the declining disease burden due to cardiovascular diseases or stagnation of neoplasms. The goal of this study is to describe the temporal changes of diabetes in the adult population of Slovakia through the three European Health Interview Survey (EHIS) waves and to assess the association between DM and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…The age-standardized prevalence of DM in EU countries showed a progressive increase between 2009 and 2019 (7.01% to 7.97%, respectively). This is line with previous studies which have reported increasing trend in DM prevalence rate over time across EU member states [25][26][27][28] . A systematic review including 10 EU member states reported that not only the prevalence of DM is increasing from 2009, but also the incidence and the mortality of the disease 3 .…”
Section: Discussionsupporting
confidence: 93%
“…The age-standardized prevalence of DM in EU countries showed a progressive increase between 2009 and 2019 (7.01% to 7.97%, respectively). This is line with previous studies which have reported increasing trend in DM prevalence rate over time across EU member states [25][26][27][28] . A systematic review including 10 EU member states reported that not only the prevalence of DM is increasing from 2009, but also the incidence and the mortality of the disease 3 .…”
Section: Discussionsupporting
confidence: 93%
“…These surveys were supervised by Eurostat, ensuring a high quality of data collection, which could be considered as a potential strength of this study. Population health surveys are a particularly useful way to draw conclusions about the respondents' health status, health behavior, and satisfaction with health services [36][37][38][39]. The analysis highlighted the longitudinal trends in influenza vaccination coverage among patients with cardiovascular diseases.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…In the present Special Issue, several articles focus on the effects of nutritional interventions on cardiovascular risk factors such as diabetes, hypertension, and increased body weight. According to Mahrouseh et al, eating vegetables several times a week in addition to performing physical exercise may reduce the risk of DM, although more lifestyle characteristics and socioeconomic conditions possibly underlie the increased prevalence of diabetes in Slovakia and other European countries [ 8 ]. The association between high fructose consumption and hypertension is controversial.…”
mentioning
confidence: 99%